The role of the thoracic spine & scapula in the shoulder impingement - Reeves, T. (coachesinfo.com, 1999)
The article deals with the following topics: - What is swimmer's shoulder? - Thoracic Spine Kyphosis - Strategies for a better swimming style What is a swimmer shoulder? Shoulder pain is the most commonly reported injury in swimmers and swimmer's shoulder is associated with pain at the front (anterior) aspect of the shoulder (Bak, 1996). Ultrasound imaging of this region shows occasional inflammation of the biceps tendon but more commonly inflammation of the supraspinatus tendon which has a stabilising effect for the shoulder especially as it moves through elevation (Gold, et al 1993). The problem with early detection of the condition is that the symptoms are often vague and non limiting to begin with and a gross change in the athlete's pattern is not noted until several months later when even non swimming movements are painful (Bak, 1996). Causes of swimmers shoulder The main factors associated with shoulder pain include swimming experience, faulty stroke technique and training errors (Bak and Fauno, 1997). The impotance of central control For the shoulder (glenohumeral joint) to function optimally it relies on a muscular balance not only at the shoulder but at the scapula (scapula) and the thoracic spine (Bak and Fauno, 1997). The aim is to begin with good central control, that is a stable and correctly positioned scapula so that maximal transition of energy can occur from the large back and arm muscles during the swimming stroke. Weakness of the scapulothoracic muscles leads to an abnormal positioning of the scapula into an upwards and forwards position. This causes a narrowing of the subacromial space, the area where impingement of the supraspinatus tendon occurs (Figure 1)(Kamkar, et al, 1993). Thoracic Spine Kyphosis The excessive rounding of the middle spine has a detrimental effect on the shoulder by affecting the position of the scapula and the length of the posterior arm muscles (Allegrucci, et al, 1994). In this position the scapula becomes abducted and therefore the muscles holding it close to the spine become lengthened. An imbalance occurs which allows the shortened muscles to be activated more easily causing an abnormal pattern of movement around the muscularly controlled shoulder (glenohumeral joint) (Sharman, 1990). What has this got to do with swimming? To achieve the optimal power for swimming it would make sense to recuit muscles that offer large mechanical advantage for little work. Examples of these muscles include; latissimus dorsi, serratus anterior, pectoralis major and deltoid (Figures 2 &3). These are used effectively in the normal, non painful shoulder but in the painful shoulder there is a notable decrease in the use of anterior deltoid and serratus anterior (Figure 4) (Scovazzo et al 1991). The other interesting points of note were that although there was no noticeable difference in the latissimus dorsi it was misfiring at different ranges of the stroke in the painful shoulder and never reached the maximal amplitude of the non painful shoulder (Figure 5a). Also there was an abnormal increase in the activity of the rhomboids in the painful shoulder which would exacerbate the impingement of the shoulder because it causes a downward tipping of the scapula (Figure 5b). That is useful if there is access to electromyograhic equipment to record these differences but what does this mean to the observer? In the painful shoulder hand entry is further from the midline with the arm lower to the water (dropped elbow). This is commonly mistaken for fatigue or laziness (Scovazzo et al 1991). The hand exits the water early because of the lack of propulsion available from the serratus anterior due to the poor position of the scapula. The rhomboids also contribute to the early exit of the hand, that is it leaves the water before it has reached the thigh and with the elbow still bent (Scovazzo, et al 1991). Another observable strategy to avoid the impingement pain is for the swimmer to increase their body roll which increases the drag, slowing them down (Beekman and Hay 1988). From the perspective of visually identifying and understanding the causes of swimmer's faults it becomes easier to correct. Although the above examples have been given due to research done with painful shoulders, if a swimmer lacks flexibility through the thoracic spine and control of the scapula these faulty stroke techniques will still occur and hopefully can be corrected before they become painful. Strategies for a better swimming style The solutions to correcting the identified faults begin centrally. The thoracic spine must have good mobility as well as resting posture. To obtain a maximal reach of the arm the thoracic spine needs to extend and side flex away from the elevating arm (Stewart, et al, 1995). This is impaired if there is an abnormal rounding of the thoracic spine (Crawford, and Jull, 1993). Next, the scapula resting position needs to be observed and corrected if the inside border is sitting more than three fingers from the spine. Observing the way the scapula moves during the swimming stroke identifies if there is a part of the range that the muscles have decreased control on the scapula thus making it susceptible to contributing to impingement (McConnell, 1994). The over-training of the pectoral muscles may lead to them shortening and therefore contributing to rounded shoulders or thoracic kyphosis. Maintain a good pectoral length as well as strength in the posterior shoulder muscles such as middle and lower trapezius avoids this problem (Figures 2 and 3)(Allegrucci, 1994). Motor control is often overlooked but the fine coordinated pattern of muscle recruitment is crucial for an efficient swimming stroke. It prevents energy wastage from unnecessary muscle activity (McConnell, 1994). Having an awareness of the arm and scapula position decreases the likelihood of instability and coupled with training which mimics the swimming patterns reinforces to the brain the exact patterns of movement required (Allegrucci, 1994). Gaining control in the normal swimming pattern can allow for more challenging tasks such as paddle training and increased distances without risks of impingement. Conclusion Training often centres around improving power, strength and increasing distances while stability and motor control are forgotten. This generally happens because the stability muscles are deep and close to the joint which makes them hard to identify and observe (See Figure 3). Their training is also based on slow, controlled patterns of movement which does not seem as rewarding as 'hard and fast'. However, 'hard and fast' is not effectively possible if the 'slow and controlled' is not in place first. Tuning a radio can be done with large turns of the dial but perfect sound comes when the dial is turned in a slow, controlled manner. Likewise gross movements of large muscles around the shoulder will still allow for movement to occur but couple this with the slow and controlled action of the deeper, smaller stabilising muscles and there is a perfect harmonious stroke.